GURU PROFESIONAL: Dalam Tugas Pokok dan Fungsi (Tupoksi) - Syarifuddin Syarifuddin (STIT AL-AMIN KREO TANGERANG, 2018)
Teacher must become inspiration for his students in creativity and model aspects. Therefore teacher must have certain personal quality standard; it covers responsibility, authority, independence and discipline. The duties of teacher are: First, as a teacher (instructional) namely he plans teaching program and carries out the program and gives score after the program was carried out. Second, as educator namely he directs the students toward adulthood level that they have perfect personalities. Third, as leader (managerial) namely he leads and controls himself, students and related community or people about the effort of directing, controlling, organizing, and participating for the program.